Sleep Disturbance in Systemic Sclerosis and the Associations Between Sleep and Pulmonary Hypertension: A Pilot Study - İpek Türk; Didem Arslan; Kezban Aslan Kara; Duygu Kurt Gök; Çağlar Emre Çağlıyan; İsmail Hanta; İlker Ünal (Türk Uyku Tıbbı Dergisi, 2024)

(untitled)
Objective: Major differences in sleep architecture are observed in patients with systemic sclerosis (SSc). The aim of this study was to investigate the sleep pattern and frequency of obstructive sleep apnea (OSA) in patients with SSc, and compare sleep patterns in patients with and without pulmonary hypertension (PH). Materials and Methods: Patients with SSc and symptoms of hypersomnia or insomnia who underwent polysomnography examinations were evaluated. The clinical data of patients were obtained from the patient files. The subjects were separated into two groups (PH-positive and PH-negative). OSA was defined as an apnea-hypopnea index (AHI) ≥5. Sleep parameters were evaluated between the groups. Results: Thirty-six patients with SSc (88.9% females; mean age: 53.1±11.2 years), 27 with diffuse SSc, and 9 with limited-type SSc were enrolled in the study. Approximately 30.6% of the patients with SSc had AHI ≥5 and 13.9% of patients had AHI ≥15. Eight patients with SSc (22.2%) had a periodic leg movement index (PMLI) above 5/h. The percentages of patients with AHI ≥5 and AHI ≥15 were 25.9% and 7.4% in the PH-negative group and 44.4% and 33.3% in the PH-positive group, respectively. The duration of the rapid eye movement sleep stage was significantly shorter in patients with SSc and PH than in those without PH (p=0.02). The percentages of patients with PMLI >5/h were 14.8% in the PH-negative group and 44.4% in the PH-positive group (p=0.086). Conclusion: Sleep disorders are more commonly observed in patients with SSc. Furthermore, OSA and PH are associated with SSc.